Peningkatan Kemampuan Membaca Sekilas Dengan Metode OK5R pada Siswa Kelas V Sekolah Dasar - Madina, Ameliza; Mayarnimar, Mayarnimar; Taufina, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to describe the skimming ability by implenting the OK5R method to the 5th grade students of Elementary School No.05 Bandar Buat, Padang. This study is a classroom action research that uses qualitative and quantitative approaches. The object of the study was the teacher and 28 students of 5th grade of State-owned Elementary School No.05 Bandar Buat. The results showed that there is an improvment in students’ reading ability from 74.4 (Enough) with level of mastery of 70.4% in cycle I,  and the result incrased 87.2 (Very good) with 92.9% level of mastery in cycle II. The percentage increase into cycle I to cycle II is 22.5%. Based on these results, it is concluded that the OK5R method can improve the skimming ability of the 5th grade Elementary School students. Keywords: Skimming Ability; OK5R Method